STEMI after Dobutamine Stress Echocardiography in Hyperthyroid State - Mahmood Mubasher; Ashfaq Patel; Mohamed Magdi; Tahir Hamid (Case Reports in Cardiology)
Uncontrolled hyperthyroidism has been associated with significant changes in cardiovascular hemodynamics. We report a case of a 39-year-old male who has been recently diagnosed with severe hyperthyroidism. He was undergoing dobutamine stress echocardiography (DSE) for evaluation of symptoms suggestive of stable angina. The exam was complicated by ST-segment elevation myocardial infarction- (STEMI-) required coronary angiography that showed mild coronary artery disease.